2017
DOI: 10.1186/s12957-017-1295-0
|View full text |Cite
|
Sign up to set email alerts
|

Associating liver partition and portal vein ligation for staged hepatectomy versus conventional two-stage hepatectomy: a systematic review and meta-analysis

Abstract: BackgroundIt is generally accepted that an insufficient future liver remnant is a major limitation of large-scale hepatectomy for patients with primary hepatocellular carcinoma. Conventional two-stage hepatectomy (TSH) is commonly considered to accelerate future liver regeneration despite its low regeneration rate. Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS), which is characterized by a rapid regeneration, has brought new opportunities.MethodsRelevant studies were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Although ALPPS had lower 1-year DFS rate, no significant difference in the 90-day mortality rate was discovered comparing the two techniques [66]. ALPPS was associated with a higher completion rate, a lower probability of tumor progression during the stage interval, and a lower insufficient regeneration rate; these findings are similar to those of previous studies [56,67,68].…”
Section: Associating Liver Partition and Portal Vein Ligation For LIVsupporting
confidence: 86%
See 1 more Smart Citation
“…Although ALPPS had lower 1-year DFS rate, no significant difference in the 90-day mortality rate was discovered comparing the two techniques [66]. ALPPS was associated with a higher completion rate, a lower probability of tumor progression during the stage interval, and a lower insufficient regeneration rate; these findings are similar to those of previous studies [56,67,68].…”
Section: Associating Liver Partition and Portal Vein Ligation For LIVsupporting
confidence: 86%
“…It has been reported that postoperative morbidity and mortality after ALPPS are 16-64 and 12-23%, respectively, with the main cause of morbidity being bile leakage and sepsis and the main cause of mortality being PHLF [66,67]. In the latest systematic review and meta-analysis by Zhou et al, 719 patients were included, and the aim was to compare the regeneration efficiency, safety, and complication rates of ALPPS and TSH.…”
Section: Associating Liver Partition and Portal Vein Ligation For LIVmentioning
confidence: 99%
“…In the first ALPPS procedures, intraoperative blood loss to partition the liver parenchyma was too high, ranging from 100 to 725 mL. Meta‐analysis confirmed the results of operation‐related outcomes . This procedure is therefore considered to be under development and modifications of the procedure and revision of its indications will be required in order to improve safety.…”
Section: Associated Liver Partition and Portal Vein Ligation For Stagmentioning
confidence: 99%
“…15 Reports of postoperative morbidity and mortality following ALPPS are 16 to 64 and 12 to 23%, respectively, with the main cause of morbidity being bile leakage and sepsis and the main cause of mortality being PHLF. 16,17 Zhou et al reviewed 719 patients comparing the regeneration efficiency, safety, and complication rates of ALPPS and TSH. The degree of FLR regeneration in ALPPS was significantly higher and the interval of the two stages in ALPPS was shorter.…”
Section: Innovative Techniques In Liver Resection Associating Liver Pmentioning
confidence: 99%